Income Inequality and Current Account Imbalances - Ranciere, Romain (IMF Working Papers; Working Paper ;, 2012)
This paper studies the empirical and theoretical link between increases in income inequality and increases in current account deficits. Cross-sectional econometric evidence shows that higher top income shares, and also financial liberalization, which is a common policy response to increases in income inequality, are associated with substantially larger external deficits. To study this mechanism we develop a DSGE model that features workers whose income share declines at the expense of investors. Loans to workers from domestic and foreign investors support aggregate demand and result in current account deficits. Financial liberalization helps workers smooth consumption, but at the cost of higher household debt and larger current account deficits. In emerging markets, workers cannot borrow from investors, who instead deploy their surplus funds abroad, leading to current account surpluses instead of deficits.